Kajian Budaya ‘Tea-Pai’ Dari Sudut Pandang Nilai Insani - Michelle Sutjiadi Sono; Listyo Yuwanto (Universitas Lambung Mangkurat, 2025)
The Tea Pai procession has become one of the 13 essential wedding ceremonies in the Thiong Hua ethnic group, considered significant and irreplaceable despite the evolving times. This ceremony involves the immediate and extended families of the bride and groom, where respect, gifts, and well-wishes for the marriage are always present in the Tea Pai. This research delves deeper into the meaning behind this procession in terms of values, symbols, and communication. These three aspects are examined from the perspective of basic human values developed by Schwartz. The study employs a literature review method covering at least the past 10 years, integrating findings and perspectives from various empirical studies conducted previously.